Development through globalization? - Deepak Nayyar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper seeks to analyze the prospects for development in a changed international context, where globalization has diminished the policy space so essential for countries that are latecomers to development. The main theme is that, to use the available policy space for development, it is necessary to redesign strategies by introducing correctives and to rethink development by incorporating different perspectives, if development is to bring about an improvement in the well-being of people. In redesigning strategies, some obvious correctives emerge from an understanding of theory and a study of experience that recognizes not only the diversity but also the complexity of development. In rethinking development, it is imperative to recognize the importance of initial conditions, the significance of institutions, the relevance of politics in economics and the critical role of good governance. Even if difficult, there is also a clear need to create more policy space for national development, by reshaping the rules of the game in the world economy and contemplating some governance of globalization. – globalization ; development ; policy space ; initial conditions ; institutions ; markets ; state ; democracy ; governance
Keywords: F02; F20; F40; O10; O19; O20; 330; Globalisierung; Entwicklung